The Social Services : The immediate problem and the way forward (London : The Socialist Medical Assocation)
1944 1944 1940s 34 pages prices accessible to them, and because they had never heard of them. The commercial theatre cannot, by its very nature, bring the theatre to the people. The same could be said of the cinema, concerts, art galleries. Museums are even now mostly free, easily accessible and very poorly patronised. This is partly due to the fact that so little is done to popularise them, and partly because many museums in this country are of interest only to the studious, and have no obvious connection with the ordinary interest of ordinary people. We have a great deal to learn from Soviet Russia, where museums are very popular. A beginning has been made with exhibitions, such as those at Charing Cross Station, on various topical subjects. 9. Provision for groups with special needs Although we envisage a shift in emphasis towards provision for the normal person, there will always be groups in society who will need special care and for many years after the war extra special provision will be needed for those who are disabled, wholly or partially, temporarily or permanently, or who have lost their homes, or relatives on whom they depended, as a result of the war. These should have a prior claim on social resources, and the special provision for them should be a public responsibility, and not left to private charity. 17 15X/2/464/1